Trends in E-Learning Usage in Vocational High Schools (SMK) - I Made Mudarta; Ketut Agustini; I Gde Wawan Sudhata; I Gusti Putu Suharta (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
Data innovation is currently progressing very rapidly in the field of education. As a result, Vocational High Schools (SMK) utilize e-learning and also information technology in carrying out teaching and learning activities. For this reason, a Systemic Literature Review (SLR) was conducted which examines what and how e-learning is researched. This research uses PRISMA (Preferred Reporting Items for Systemic and Meta-Analysis) guidelines, by searching for scopus indexed articles in the 2019-2023 range involving a total of 193 articles. After the screening process, 20 articles were obtained which were then analyzed in accordance with the Research Question (RQ) that had been formulated. The objectives of this examination are (1) To assess and describe the effect of e-learning implementation through Edmodo Stage (2) To determine the factors that influence the continuity of e-learning at work on students' understanding and learning achievement in the Edmodo field. These results have limitations in terms of the scope of data sources and the depth of study on the material discussed. So this research provides opportunities for further researchers both in development design and SLR.